Biodegradable polydioxanone stents in the treatment of adult patients with tracheal narrowing - Stehlik, Ludek; Hytych, Vladislav; Letackova, Jana; Kubena, Petr; Vasakova, Martina (BMC pulmonary medicine, 2015)
BACKGROUND: Biodegradable stents that disintegrate after a period of time are expected to be well tolerated and have advantages over other stents that are more commonly used in practice today. Polydioxanone is a biodegradable polymer that is widely used during surgery with absorbable sutures. METHODS: We present cases from the first four patients to undergo a tracheal polydioxanone stent insertion. Indications included significant non-malignant tracheal stenosis in cases where primary surgical treatment was not possible. The stents were implanted using rigid bronchoscopy and patients received regular follow-ups as needed. This use of biodegradable stents in adult patients was a novel, previously untested approach. The study was approved by the Institutional Ethics Committee and was based on a project entitled; "Biodegradable stents in the management of stenoses of large airways" (project NT 14146-3/2013). RESULTS: Six biodegradable stents were implanted in four patients with benign stenoses. No technical difficulties occurred and no serious or life-threatening events were recorded. All patients reported some benefit from treatment. CONCLUSION: Polydioxanone tracheal stents can be considered when a need for temporary support is expected, and as an alternative to other stents if the latter could compromise the patient. Owing to limited experience and observed disadvantages, further research is needed to fully assess this treatment. TRIAL REGISTRATION: This work is based on project NT14146 - Biodegradable stents in the management of stenoses of the large airways (2013-2015, MZ0/NT), registered from May 1, 2013 in The Research and Development and Innovation Information System of the Czech Republic and in ClinicalTrials.gov, reg. no. NCT02620319, December 2, 2015.
Keywords: biokompatibilní materiály; Tracheal Stenosis; trachea; Humans; Polydioxanone; lidé středního věku; Middle Aged; Bronchoscopy; Czech Republic; bronchoskopie; polydioxanon; stenty; Trachea; mužské pohlaví; Česká republika; Biocompatible Materials; výsledek terapie; Stents; Treatment Outcome; ženské pohlaví; lidé; Aged; senioři; Male; stenóza průdušnice; Female